Controlling schistosomiasis with praziquantel: How much longer without a viable alternative? - Robert Bergquist; Jürg Utzinger; Jennifer Keiser (BMC, 2017)
Abstract The current approach of morbidity control of schistosomiasis, a helminth disease of poverty with considerable public health and socioeconomic impact, is based on preventive chemotherapy with praziquantel. There is a pressing need for new drugs against this disease whose control entirely depends on this single drug that has been widely used over the past 40 years. We argue that a broader anthelminthic approach supplementing praziquantel with new antischistosomals targeting different parasite development stages would not only increase efficacy but also reduce the risk for drug resistance. Repositioning drugs already approved for other diseases provides a shortcut to clinical trials, as it is expected that such drugs rapidly pass the regulatory authorities. The antischistosomal properties of antimalarial drugs (e.g., semisynthetic artemisinins, synthetic trioxolanes, trioxaquines and mefloquine) and of drugs being developed or registered for other purposes (e.g., moxidectin and miltefosin), administered alone or in combination with praziquantel, have been tested in the laboratory and clinical trials. Another avenue to follow is the continued search for new antischistosomal properties in plants. Here, we summarise recent progress made in schistosomiasis chemotherapy, placing particular emphasis on repositioning of existing drugs against schistosomiasis.